Perancangan Sistem Monitoring Perjalanan Dinas Pada Komisi Pemilihan Umum Provinsi Sumatera Utara Berbasis Web - Pinka, Maura Morena; Irawan, Muhammad Dedi; Eka, Muhammad (Universitas Islam Negeri Sumatera Utara, 2024)
In general, official travel is travel undertaken by employees in a company that is related to official work duties. The official duties of the North Sumatra Province General Election Commission still use manual methods by recording documents in the official travel system. And they do not yet have an effective monitoring system designed to facilitate their activities, so that the official travel system does not run according to its development. The method used is waterfall because it has a design flow to find out directly the needs of the secretary, head of section, head of sub-section, treasurer to meet clear needs. With the design of this monitoring system, North Sumatra provincial KPU employees can search for official travel data easily and quickly. These functional requirements can be accessed by Admin, employees and officials.Keywords: Business trips, Monitoring systems, Waterfall.